IMPLEMENTASI SENAM OTAK (BRAIN GYM) TERHADAP PERUBAHAN FUNGSI KOGNITIF WANITA POST MENOPAUSE DI DESA MELEBUNG - Ovari, Isna; Waruwu, Arlina; Ayudytha, Awaliyah Ulfah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
As age increases, many processes of development and growth occur in humans which will stop at one stage, so that in the future there will be many changes in body functions, both physical and psychological, due to the aging process. Brain gym is a form of exercise to improve cognitive function. Objective: To determine the implementation of Brain Gym on changes in the cognitive function of post-menopausal women in Melebung District. Method: This research method uses a descriptive method that uses a nursing care approach for 3 people. Cognitive function was observed with the Mini Mental State Examination (MMSE) before and after intervention. Conclusion: The results of the study show changes in cognitive function after being given Brain Gym intervention in post-menopausal women. Suggestion: Providing Brain Gym intervention can be an effective way to control cognitive function in post-menopausal women.